Enhanced education on geology by 3D interactive virtual geological scenes - Yuan Fang; Yuxin Li; Lei Fan (Computers & Education: X Reality)
Virtual Reality (VR) technology is a computer simulation system that leverages real-life data to create and immerse users in virtual worlds. Widely utilized across various industries, VR technology plays a crucial role in interactive training and education on construction-related subjects such as site visualization, construction processes, and health and safety. It also serves as a beneficial supplementary tool for conducting field trips, an essential component of civil engineering courses. This study showcases our development and implementation of a virtual geology site for geology education utilizing dense point cloud data captured at an actual geology site and a web-based VR tool. We utilized Potree, a free open-source web-graphics-library-based point cloud renderer designed for large point clouds, to create our virtual environment. Geological features, measurements, annotations and quizzes were incorporated to enhance student engagement and teaching effectiveness. To evaluate the impact of the developed virtual geology site, we conducted an anonymous questionnaire survey among students who had participated in field trips and experienced the virtual environment. Their feedback served to validate the effectiveness of the virtual geology site in providing an interactive and enhanced learning experience. Additionally, the study explores the potential for VR to overcome practical challenges associated with traditional field trips, such as accessibility and safety concerns, making it a versatile tool for ongoing and future educational applications in geology and beyond.